User Satisfaction with Personalised Internet Applications - Bauernfeind, Ulrike (Forschungsergebnisse der Wirtschaftsuniversitaet Wien, 2018)
The study focuses on user satisfaction with websites and personalised internet applications in particular. The abundance of information on the web is increasing more and more. Therefore, the significance of websites targeting the users' preferences, like personalised Internet applications, is rising. The aim of this study was to find out which factors determine user satisfaction with personalised internet applications. Factors like the usefulness of the information or trust towards how personal information is handled were considered. A large-scale user survey evaluating three internet applications (from the travel, e-learning and real estate domains) was conducted. Expert opinions were collected to complement the results and provide insights from users' and experts' points of views.